The interconnection between individual components of technical value and competitive results of the best aesthetic gymnastics groups in the world - Bulgacheva, P.; Shugol, T.; Novikova, L. (Theory and Practice of Physical Culture, 2024)
The purpose of the research is to determine the interconnection between technical and artistic value, execution of the competition programs and the final score of the best aesthetic gymnastic groups in the world.